2015
DOI: 10.1051/0004-6361/201425285
|View full text |Cite
|
Sign up to set email alerts
|

Shear instabilities in a fully compressible polytropic atmosphere

Abstract: Shear flows have a significant impact on the dynamics in an assortment of different astrophysical objects, including accretion discs and stellar interiors. Investigating shear flow instabilities in a polytropic atmosphere provides a fundamental understanding of the motion in stellar interiors where turbulent motions, mixing processes, and magnetic field generation take place. Here, a linear stability analysis for a fully compressible fluid in a two-dimensional Cartesian geometry is carried out. Our study focus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 27 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, the boundary conditions introduced in equation (5) restrict the shear profile to values of L u that will result in a low enough value of the z-derivative of u 0 at the boundaries. A visualisation of the general form of shear, density and temperature profiles used in this paper can be found in Witzke, Silvers & Favier (2015). The force term, F, in equation (2) aims to model external forces resulting from large-scale global effects (such as Reynolds stresses associated with thermal convection in global-scale calculations for example) that are not included in our local approach.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the boundary conditions introduced in equation (5) restrict the shear profile to values of L u that will result in a low enough value of the z-derivative of u 0 at the boundaries. A visualisation of the general form of shear, density and temperature profiles used in this paper can be found in Witzke, Silvers & Favier (2015). The force term, F, in equation (2) aims to model external forces resulting from large-scale global effects (such as Reynolds stresses associated with thermal convection in global-scale calculations for example) that are not included in our local approach.…”
Section: Modelmentioning
confidence: 99%
“…This was achieved by changing U 0 = 0.07 and 1/L u = 60, and the dynamical viscosity was fixed to be 10 −5 . We compared the growth rate and the most unstable mode predicted by means of a linear stability analysis as used in Witzke et al (2015) to that found in all cases of the secular instability. Furthermore, we checked that the instability is a consequence of the destabilising mechanism at low Péclet numbers, by conducting test cases with the same dynamical viscosity as used in cases O to R but C k = 0.0002.…”
Section: Secular Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…We do not consider shear instabilities triggered by thermal diffusion for which larger values of Ri can be used (Dudis 1974;Zahn 1974;Lignières et al 1999). Because the 1/4 criterion is a necessary, but not sufficient, requirement for instability we also solve the corresponding linear stability problem based on the approach used in Witzke, Silvers & Favier (2015) in addition to conducting the non-linear calculations. For simplicity, the Prandtl number is fixed to be unity whereas the dimensionless thermal diffusivity C k is varied from 10 −4 to 10 −5 .…”
Section: Linear Regimementioning
confidence: 99%
“…For simplicity, the Prandtl number is fixed to be unity whereas the dimensionless thermal diffusivity C k is varied from 10 −4 to 10 −5 . Taking the previous linear study by Witzke, Silvers & Favier (2015) into account, our parameters satisfy the following requirements: To ensure a stable stratification the polytropic index is set to be m = 1.6, the amplitude U 0 of the shear flow is chosen such that the Mach number in the middle of the domain remains less than 0.08, which avoids additional stabilisation by compressible effects. Furthermore, we take the initial Péclet number, which we define as…”
Section: Linear Regimementioning
confidence: 99%